Biological study and effects of some food media and temperature on the survival and development of Corcyra cephalonica (Staint) - Tauthong, P. (Kuala Lumpur (Malaysia), 2015)
The results showed that the incubation period was 4.3 days. The larva molted 5.7 times. The time required for the larval and pupal development was 32.93 and 9.6 days respectively. Longevity of the male and female moth was 9.33 and 4.78 days respectively. Life cycle of the insect was about 47.31 days. The comparative studies of development on different food media at room temperature (31.7 deg , 72.2 percent R.H.) indicated that both broken maize and broken rice appeared to be the best media for growth and development of rice moth. The effects of temperature on the development of rice moth on 4 food media (rice, broken rice, glutinous rice, and broken maize) were investigated at 20 and 30 deg , 85-95 percent R.H. The development periods of insects at 20 deg were prolonged compared to those at 30 deg